COLORED COTTON TO SUPPORT THE SUSTAINABILITY OF THE BRAZILIAN TEXTILE INDUSTRY - GARCIA, S.; NÄÄS, I. A.; VENDRAMETTO, O. (Revista Brasileira de Engenharia de Biossistemas, 2012)
The fashion segment is formed by various enterprises chains which work together, although in independent form for the success of the production chain. Using its high capillarity these chains are formed by companies which interacts with various with various lines of business and manufacturing of various products. There are various forms of product distribution used in this network. This research aimed to investigate the application of the sustainability concepts in the production and distribution of fashion garments. The research was done from an exploratory study and a case study which was based in five interviews. Understanding the sustainability issue in the various segments that make up the network of fashion companies is presented and discussed, being proposed colored cotton to industry sustainability.